To solve the expression 3 squared times 3 squared, we first need to calculate each squared term separately.
3 squared, or 32, is equal to 3 times 3, which is 9. Therefore, we have:
32 = 9
Now we calculate the expression:
32 × 32 = 9 × 9 = 81
Alternatively, we can use the law of exponents, which states that when you multiply two expressions with the same base, you add their exponents. In our case:
32 × 32 = 32+2 = 34
Calculating 34 gives us:
34 = 3 × 3 × 3 × 3 = 81
Thus, the final answer to the question is:
81